Novel and practical synthesis of vonoprazan fumarate. Issue 12 (18th June 2017) - Yu, Qian-Ying; Zeng, Huang; Yao, Kai; Li, Jian-Qi; Liu, Yu
ABSTRACT: A novel and practical strategy for the synthesis of vonoprazan fumarate1, a novel potassium-competitive acid blocker, has been developed. Vonoprazan fumarate was obtained through a four-step process starting from 5-(2-fluorophenyl)-1H-pyrrole-3-carboxylate and including ester hydrolyzing, methylamine substitution, sulfonyl chloride substitution, and amide reduction. Key to the strategy is the amide reduction taking a novel and practical protocol. The main advantages of this route include two parts: controllable impurity and acceptable overall yield. GRAPHICAL ABSTRACT: